Prunus spinosa Extract Loaded in Biomimetic Nanoparticles Evokes In Vitro Anti-Inflammatory and Wound Healing Activities - Mattia Tiboni; Sofia Coppari; Luca Casettari; Michele Guescini; Mariastella Colomba; Daniele Fraternale; Andrea Gorassini; Giancarlo Verardo; Seeram Ramakrishna; Loretta Guidi; Barbara Di Giacomo; Michele Mari; et al. (Nanomaterials, 2020)
Prunus spinosa fruits (PSF) contain different phenolic compounds showing antioxidant and anti-inflammatory activities. Innovative drug delivery systems such as biomimetic nanoparticles could improve the activity of PSF extract by promoting (i) the protection of payload into the lipidic bilayer, (ii) increased accumulation to the diseased tissue due to specific targeting properties, (iii) improved biocompatibility, (iv) low toxicity and increased bioavailability. Using membrane proteins extracted from human monocyte cell line THP-1 cells and a mixture of phospholipids, we formulated two types of PSF-extract-loaded biomimetic vesicles differing from each other for the presence of either 1,2-dioleoyl-sn-glycero-3-phosphocholine (DOPC) or 1,2-dioleoyl-sn-glycero-3-phospho-(1′-rac-glycerol) (DOPG). The biological activity of free extract (PSF), compared to both types of extract-loaded vesicles (PSF-DOPCs and PSF-DOPGs) and empty vesicles (DOPCs and DOPGs), was evaluated in vitro on HUVEC cells. PSF-DOPCs showed preferential incorporation of the extract. When enriched into the nanovesicles, the extract showed a significantly increased anti-inflammatory activity, and a pronounced wound-healing effect (with PSF-DOPCs more efficient than PSF-DOPGs) compared to free PSF. This innovative drug delivery system, combining nutraceutical active ingredients into a biomimetic formulation, represents a possible adjuvant therapy for the treatment of wound healing. This nanoplatform could be useful for the encapsulation/enrichment of other nutraceutical products with short stability and low bioavailability.